A comparison of internal jugular vein cannulation versus supraclavicular brachiocephalic vein cannulation using ultrasound guidance - Zulfiqar Ali,; Abdul Waheed Mir,; Iqra Nazir,; Sajad Hussain Arif,; Altaf Mir,; Mir Mohsin,; Zoya Sehar,; Shahid Ahmad Mir, (Asian Journal of Medical Sciences, 2024)
Background: Ultrasound has become the standard of care for the insertion of central venous catheters (CVCs) in the intensive care unit. With the introduction of ultrasonography in CVC insertion, there has been an improvement in the success rate and a dramatic decrease in the rate of complications. Aims and Objectives: The aim of this study was to compare the safety and ease of insertion of ultrasonically guided cannulation of the internal jugular vein (IJV) with that of the supraclavicular subclavian vein (SCV) in adult patients undergoing various surgical procedures. Materials and Methods: All the patients in whom central venous cannulation was planned were assigned to two groups. Group I underwent ultrasound-guided IJV while as Group II underwent cannulation ultrasound-guided SCV cannulation. A comparison was made between the two groups, of the success rates, durations of procedure, number of attempts at needle redirections, difficulties if any during insertion of guidewires, and the complications encountered. Results: The IJV group had a higher proportion of first-attempt success (93.2% versus 62.7%). The IJV group had a lesser incidence (3.2%) of complications such as guidewire progression and needle redirections compared with SCV (15.2%). The frequency of adverse events did not differ between the two study groups with an incidence in 3.2% in IJV group and 9.6% in the subclavian group. Higher first-attempt success rates and fewer procedural complications were seen with ultrasound-guided IJV. Conclusion: IJV central venous catheterization is an easier and less invasive and less risky procedure for patients.